THE ROLE OF ILLUSTRATION IN ENHANCING READING COMPREHENSION OF COLLEGE STUDENTS - Purwanti Purwanti; Bachrudin Musthafa (Universitas Pendidikan Indonesia, 2019)
The low interest in reading makes the students have less reading frequency, thus the students are not much experienced in reading correctly. This problem leads them to have a low level of comprehension skill. This research is intended to check and find out whether the students can improve their level of comprehension skill after being given a certain teaching completed with some treatments. The research investigates the impact of using illustrations and its effects on students’ attitude. The data are in the form of scores and students’ opinions. Score data is obtained from the result of pretest and posttest which are calculated quantitatively, while questionnaire and interview are analyzed qualitatively to support the explanation. The results show that there is significant enhancement in student reading skills not only of the expert readers but also of the average readers and of poor readers.